Analysis of Foundation Pit Design of Metro Station in Complex Environment - Yunchao Tao (Advances in Materials Science and Engineering)
The complex engineering geological conditions and the surrounding environmental conditions of the existing subway lines and adjacent buildings have significantly deepened the difficulty of metro station foundation pit design and construction. Based on the foundation pit project of Luboyuan Station of Nanjing Metro Line 9, this study chooses a reasonable foundation pit support design scheme to carry out related research by analyzing the site geological environmental conditions. Through the analysis and evaluation of the engineering geological conditions of the engineering site, the engineering geological problems that may occur in the process of construction are given. According to the lithologic characteristics of the site strata, the hydrogeological conditions, and the features of the underground engineering structure, the design of the foundation pit supporting system is optimized and analyzed. The results show that making full use of the geological features of strata and adopting effective support methods can ensure the safety of foundation pit construction, reduce the cost of engineering description, and shorten the construction period, which can be used as a reference for similar projects and construction.